Mastering web application development with Express : a comprehensive guide to developing production-ready web applications with Express - Vladutu, Alexandru (Community experience distilled., 2014)
If you are a Node.js developer who wants to take your Express skills to the next level and develop high performing, reliable web applications using best practices, this book is ideal for you. The only prerequisite is knowledge of Node.js.